An assessment of Qatar's coral communities in a regional context. Issue 2 (30th April 2016) - Burt, John A.; Smith, Edward G.; Warren, Christopher; Dupont, Jennifer
Abstract: Qatar's once extensive coral communities have undergone considerable change in recent decades. We quantitatively surveyed three coral assemblages in Qatar to assess current status, and compared these against 14 sites in Bahrain and the United Arab Emirates to evaluate Qatar in a larger biogeographic context. Umm Al-Arshan had the highest species richness of 17 sites examined in the southern Arabian Gulf, as well as the highest coral cover and the only Acropora observed on sites in Qatar. Coral cover and richness were more modest at Fuwayrit and Al-Ashat, reflecting greater impacts from earlier stress events. Two distinct communities were identified across the southern Gulf, with Umm Al-Arshan clustering with high-cover, mixed merulinid/poritid assemblages that were less impacted by earlier bleaching and long-term stress, while Fuwayrit and Al-Ashat grouped with a lower-cover, stress-tolerant community characteristic of more extreme environments in the southern Gulf. We recommend implementation of a nation-wide baseline assessment of coral communities to guide development of an MPA network and long-term coral monitoring program for Qatar.